Modeling and control of magnetic levitation system via fuzzy logic controller - Ishaque, K. (IEEE, 2011)
Fuzzy logic controller (FLC) is an attractive alternative to existing classical or modern controllers for designing the challenging Non-linear control systems. It does not require any system modeling or complex mathematical equations governing the relationship between inputs and outputs. Fuzzy rules are very easy to learn and use, even by non-experts. It typically takes only a few rules to describe systems that may require several lines of conventional software code, which reduces the design complexity. By considering these advantages, this paper presents the design and analysis of a FLC controller for the magnetic levitation system. Additionally, a classical PID controller is also designed to compare the performance of both types of controllers. Results reveal that FLC found to give better transient and steady state results compare to the classical PID.